Reproductive and Child Health status in EAG States, India (A District Level Analysis) - Som, Kalyan Sundar; Mishra, R. P. (National Geographical Journal of India, 2022)
Reproductive and child health status (RCH) has been analysed both at state level and district level in eight Empowered Action Group of States (EAG states) of India in this study. The RCH value calculated in these EAG states is by using composite z-score method. Among these EAG states Uttar Pradesh and Bihar, the most populous states of the country, are in very poor condition, while Uttarakhand and Chhattisgarh, the new and small states, are in better condition in terms of RCH status. At district level Baharaich and Balrampur districts of Uttar Pradesh are in the worst condition, while Dehradun of Uttarakhand is in the good condition in terms of RCH status. Several determinants have an impact on the RCH status in different states of our country. To find out the relative significance of these determinants, the multiple regression analysis has been made in this study. The most significant determinants are literacy and education, family size, accessibility, safe delivery and quality care